2020
DOI: 10.3803/enm.2020.35.1.157
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Prognosis of Pheochromocytoma/Paraganglioma in Korea: A Nationwide Study Based on the National Health Insurance Service

Abstract: Background: Pheochromocytomas and paragangliomas (PPGLs) are rare endocrine tumors originating from chromaffin cells. PP-GLs are associated with a high mortality rate and several complications. To date, no epidemiological studies have been conducted on PPGLs in Asia. This study aimed to investigate the epidemiology and prognosis of PPGLs in Korea using nationwide data. Methods: Using the National Health Insurance Service Database, subjects with a principal diagnosis of PPGLs on two or more occasions between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 27 publications
(39 reference statements)
2
45
2
Order By: Relevance
“…Patients with metastatic PPGLs have high morbidity and mortality rates due to the excessive catecholamines, and patients with metastatic PPGLs have a significantly lower 5-year survival rate compared to patients without metastases (90% vs. 60%) [ 31 , 32 ]. Similarly, a recent nationwide population-based epidemiological study in South Korea showed the hazard ratio for mortality of patients with metastatic PPGLs was twice higher compared to patients without metastatic PPGLs [ 1 ]. The common metastatic sites of metastatic PPGLs are the regional and distant lymph nodes, bone, liver, and lungs [ 33 , 34 ].…”
Section: Discussion Of the Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with metastatic PPGLs have high morbidity and mortality rates due to the excessive catecholamines, and patients with metastatic PPGLs have a significantly lower 5-year survival rate compared to patients without metastases (90% vs. 60%) [ 31 , 32 ]. Similarly, a recent nationwide population-based epidemiological study in South Korea showed the hazard ratio for mortality of patients with metastatic PPGLs was twice higher compared to patients without metastatic PPGLs [ 1 ]. The common metastatic sites of metastatic PPGLs are the regional and distant lymph nodes, bone, liver, and lungs [ 33 , 34 ].…”
Section: Discussion Of the Recommendationsmentioning
confidence: 99%
“…Pheochromocytomas and paragangliomas (PPGLs) are rare chromaffin cells-derived tumors that originated from the adrenal medulla and the extra-adrenal sympathetic or parasympathetic paraganglia, respectively. The overall annual incidence of PPGLs is estimated to be two to eight cases per million, and the recent report in Korea showed the annual incidence of 1.8 cases per million [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Despite their low prevalence, phaeochromocytomas are associated with a high mortality rate and several complications. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…There are various reports in the literature regarding the male to female ratio. Some studies reported no significant difference in prevalence between the sexes, while findings from another study demonstrated a slight female preponderance [6,8].…”
Section: Epidemiologymentioning
confidence: 88%
“…A more recent study from Korea showed that the paragangliomas and pheochromocytomas have the prevalence of 2.13 per 100,000 persons and an age-standardized incidence of 0.18 per 100,000 person-years [6].…”
Section: Epidemiologymentioning
confidence: 99%